Knowledge Management Practice on Digital Financial Innovation - Dahal Chhetri, Ashmita (BMC Journal of Scientific Research, 2024)
The study examines the influence of knowledge management (KM) on digital financial innovation in banks. The research was conducted in Bharatpur, involved surveying 161 bank employees at various management levels through purposive sampling. The study found that digital financial innovations significantly enhance customer satisfaction, with popular trends such as AI, digital platform integration, advanced data analytics, and blockchain technology. Banks effectively manage knowledge sources to improve performance and demonstrate competitive responsiveness. The banking sector actively promotes knowledge integration among employees and external partners, emphasizing the importance of knowledge-sharing cultures. Statistical analysis revealed moderate positive relationship between knowledge utilization, acquisition, and integration with digital financial innovation. The study identified barriers to KM, such as organizational culture, technological infrastructure, regulatory constraints, and worker resistance. It also identified significant KM challenges for digital financial innovation, including internal expertise, resistance to change, integration issues, and security concerns. Regular training, workshops, and internal newsletters were the main methods for disseminating knowledge about innovations. The study concludes that banks should prioritize customer needs and invest heavily in digital financial innovation to maintain competitiveness and enhance customer satisfaction